High prevalence of Chlamydia trachomatis and Neisseria gonorrhoeae infections in anal and pharyngeal sites among a community-based sample of men who have sex with men and transgender women in Lima, Peru. Issue 1 (6th January 2016) - Leon, Segundo R; Segura, Eddy R; Konda, Kelika A; Flores, Juan A; Silva-Santisteban, Alfonso; Galea, Jerome T; Coates, Thomas J; Klausner, Jeffrey D; Caceres, Carlos F
Abstract : Objectives: This study aimed to characterise the epidemiology of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections among men who have sex with men (MSM) and transgender women (TW) in Lima, Peru. Setting: Cross-sectional study in Lima, Peru. Participants: We recruited a group of 510 MSM and 208 TW for a subsequent community-based randomised controlled trial. The presence of CT and NG were evaluated using Aptima Combo2 in pharyngeal and anal swabs. We also explored correlates of these infections. Primary and secondary outcome measures: Study end points included overall prevalence of C. trachomatis and N. gonorrhoeae in anal and pharyngeal sites. Results: Overall prevalence of CT was 19% (95% CI 16.1% to 22.1%) and 4.8% (95% CI 3.3% to 6.6%) in anal and pharyngeal sites, respectively, while prevalence of NG was 9.6% (95% CI 7.5% to 12.0%) and 6.5% (95% CI 4.8% to 8.5%) in anal and pharyngeal sites, respectively. Conclusions: The prevalence of each infection declined significantly among participants older than 34 years (p<0.05). Efforts towards prevention and treatment of extraurogenital chlamydial and gonococcal infections in high-risk populations like MSM and TW in Lima, Peru, are warranted. Trial registration number: NCT00670163; Results.